IMPLEMENTASI ABSS PREMIER V20 PADA LAPORAN KEUANGAN UMKM BISNIS JUAL BELI PAKAIAN - Laraswati, Dewi; Indarti, Indarti (PROFITABILITAS, 2022)
Good management of accounting data and following accounting standards is an important aspect for the progress of a business, especially in terms of preparing financial reports. However, one of the problems faced by MSMEs, especially small businesses, is generally limited in understanding how to manage financial accounting data up to preparing financial reports. The methods used in this research are observation, interviews, and literature studies related to the research themes taken. Financial statements are very important for the company, with the existence of financial statements, the company can find out the profit and loss in each period and the company has innovations in the future. Financial statements that are made manually, are considered inefficient and the work is relatively slow. Therefore, the company continues to innovate and find ways so that every data processing can be done effectively and efficiently, and without wasteping time. In thisproblem, companies need modern software to support activities in the financial recording process, this is also driven by technological advances. Accounting software is very useful for companies, because in addition to saving time, the final result of such financial data has proven to be accurate. The accounting software applied to this final project is ABSS Premiere version 20. The purpose of using the software is to minimize errors because the final result in recording finances is because the method used has been posted automatically, as well as saving time and energy in financial recording activities. With the observation and interview methods, the author wasable to change the recording of keuangan from manual to computerized at the clothing store, as well as the literature study method as a reference related to the theory to be used.